Learning How to Feel. Children’s Literature and Emotional Socialization, 1870-1970, por Ute Frevert, Pascal Eitler, Stephanie Olsen et al., - Vallgårda, Karen (Historia y Memoria de la Educación, 2015)
Review of Ute Frevert, Pascal Eitler, Stephanie Olsen et al., Learning How to Feel. Children’s Literatureand Emotional Socialization, 1870-1970